How individuals change during internet‐based interventions for depression: A randomized controlled trial comparing standardized and individualized feedback. Issue 1 (27th November 2019) - Zagorscak, Pavle; Heinrich, Manuel; Bohn, Johannes; Stein, Jana; Knaevelsrud, Christine
Abstract: Background: Standardized and individualized Internet‐based interventions (IBI) for depression yield significant symptom improvements. However, change patterns during standardized or individualized IBI are unknown. Identifying subgroups that experience different symptom courses during IBI and their characteristics is vital for improving response. Methods: Mildly to moderately depressed individuals according to self‐report ( N = 1, 089) were randomized to receive module‐wise feedback that was either standardized or individualized by a counselor within an otherwise identical cognitive‐behavioral IBI for depression (seven modules over six weeks). Depressive symptoms were assessed at baseline and before each module (Patient Health Questionnaire; PHQ‐9). Other individual characteristics (self‐report) and the presence of an affective disorder (structured clinical interview) were assessed at baseline. Growth mixture modeling was used to identify and compare subgroups with discernable change patterns and associated client variables across conditions. Results: Model comparisons suggest equal change patterns in both conditions. Across conditions, a group of immediate (62.5%) and a group of delayed improvers (37.5%) were identified. Immediate improvers decreased their PHQ‐9 score by 5.5 points from pre to post, with 33% of improvement occurring before treatment commenced. Delayed improvers were characterized by stable symptom severity during the first two modules and smaller overall symptom decrease (3.4 points). Higher treatment expectations, a current major depressive disorder (interview), and lower social support were associated with delayed improvement. Conclusion: Internet‐based interventions for depression with individualized and with standardized feedback lead to comparable patterns of change. Expectation management and bolstering of social support are promising strategies for individuals that are at risk for delayed improvement. Abstract : The study investigates depressive symptom courses during IBI for depression with individualized versus standardized feedback. Across conditions, a group of immediate (62.5%) and a group of delayed improvers (37.5%) were identified. Higher treatment expectations, a current major depressive disorder and lower social support were associated with delayed improvement.